Keindahan Di Balik Tragedi - I Made Saryana (Mudra Jurnal Seni Budaya, 2008)
The use of transportation facilities represents the metaphor of “double-sides sword”; on the one hand it gives usefulness, on the other hand it gives destructiveness. An ideal dualism of modern culture achievement, and the tragedy inherently implied. While the comfort of traveling embodies the positive side, the pollution and car accident re- present the negative side. We have no other alternative, nevertheless, since the modern culture demanded such a high mobility that the use of modern transportation is unavoidable. Almost everyday we heard and read in mass media about various acci- dent of car crashes. Even in minor cases, the victims or damages are al- ways unavoidable. In a huge scale, the accident of transportation might take a great many victims and material damages. Consequently, the sur- vivors or the relatives of the casualties might experience mourning and sadness, even trauma. These are what we might call tragedies, the ones causing human suffering. Viewed as an event, accident left at least two realities: the one asso- ciated with mental/psychological implication and the other related to the factual objects that create automatically new “meaning”, even trans- formation to other “meaning”. In my opinion, the wrecked cars, or those with the paint peeled off, or the chassis detached, or the whole body burnt out, represent the factual reality of the objects undergone the transformation of “meaning”. A paradoxical reality of meaning: Between the one referring to the traumatic side, and the other that sig- nify the visually artistic side. It is on this paradoxical meaning that I based my creative exploration to create my photographic artworks. Observation might inspire an unexpected visual composition. By photographing the most unique and the most interesting of the bro- ken pieces of the wrecked cars using the close-up function, an artistic and aesthetical photographic artwork might be created. That is the reason for me to choose the title “Beauty behind Tragedy”.